Pengaruh Penggunaan E-Wallet terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman - Alrianisti Rafa Athaya; Dian Isnawati; Aldila Krisnaresanti (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study was conducted to analyze the influence of e-wallet usage on the consumer behavior of students at the Faculty of Economics and Business, Jenderal Soedirman University. The development of digital payments has driven increased e-wallet usage among students, as they are perceived as more practical, efficient, and faster for transactions. This convenience is expected to influence student consumer behavior. This study employed a quantitative approach with a survey method. Sampling was conducted using a purposive sampling technique, with 50 students who had used e-wallets for at least the past three months and made at least three transactions per month. Data were collected through an online questionnaire and then analyzed using simple linear regression. The results showed that e-wallet usage has a positive and significant influence on student consumer behavior. These findings indicate that the higher the level of e-wallet usage, the greater the tendency for student consumer behavior. This research is expected to provide students with considerations to be more prudent in using e-wallets and to better manage their finances in the digital era.